Assessment of the quality of nursing work life and its related factors among critical care nurses - Alzoubi, Majdi M.; Al-momani, Shaimaa; Al-Mugheed, Khalid; Owiedat, Islam; Shosha, Ghada Mohammad Abu; Alabdullah, Amany Anwar Saeed; Alsenany, Samira Ahmed; Abdelaliem, Sally Mohammed Farghaly (Frontiers in Public Health, 2024)
Background: Quality of work life (QWL) refers to the degree to which employees contribute to the organization's goals while also experiencing personal and professional satisfaction. This study conducted to evaluate the quality of nursing work life (QNWL) level and its associated factors among nurses working in critical care units. Methods: A convenience sample technique among critical care nurses in Jordan by using a cross-sectional, descriptive design. A self-reported questionnaire was used. A Pittsburgh Sleep Quality Index (PSQI), and the Andersson and Lindgren questionnaires scale were used in data collection. Results: The total mean scores of QNWL were M = 86.17 (SD = 35.12), which is slightly below the expected middle value (87.5). The nurses have a higher psychological relation, M = 18.28 (SD = 8.99), whereas they have the lowest competence development, M = 11.44 (SD = 5.56). There was statistical significance between workplace noise, and workplace sources of noise, quality of sleep and QNWL. Conclusion: The outcomes also highlighted the significance of undertaking additional interventional research studies in the future in order to identify practical strategies to improve nurses QNWL. As a result, the nursing care given to the patients and their families may be improved.